2021
DOI: 10.1101/2021.03.01.433316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct cochlear recordings in humans show a theta rhythmic modulation of the auditory nerve by selective attention

Abstract: The architecture of the efferent auditory system enables prioritization of strongly overlapping spatiotemporal cochlear activation patterns elicited by relevant and irrelevant inputs. So far, attempts at finding such attentional modulations of cochlear activity delivered indirect insights in humans or required direct recordings in animals. The extent to which spiral ganglion cells forming the human hearing nerve are sensitive to selective attention remains largely unknown. We investigated this question by test… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Recent studies using non-invasive electrophysiology have shown that auditory activity at putative subcortical processing stages can be measured for complex natural sounds (such as speech; [19][20][21][22]. Furthermore, this subcortical activity can even be modulated by attention (19,20,23). Interestingly, top-down attentional modulations of auditory activity can already be detected at the hair cells in the inner ear measured as otoacoustic activity (faint sounds emitted by the outer hair cells; see 24).…”
Section: Modelling Of Subcortical Activity Reveals a Predominant Tracking Of The Modulation Rate Of Speechmentioning
confidence: 99%
“…Recent studies using non-invasive electrophysiology have shown that auditory activity at putative subcortical processing stages can be measured for complex natural sounds (such as speech; [19][20][21][22]. Furthermore, this subcortical activity can even be modulated by attention (19,20,23). Interestingly, top-down attentional modulations of auditory activity can already be detected at the hair cells in the inner ear measured as otoacoustic activity (faint sounds emitted by the outer hair cells; see 24).…”
Section: Modelling Of Subcortical Activity Reveals a Predominant Tracking Of The Modulation Rate Of Speechmentioning
confidence: 99%